A Demonstration of TouchLight, an Imaging Touch Screen and Display for Gesture-Based Interaction - Wilson, Andy (UIST '04 - Adjunct Proceedings of the 17th annual ACM Symposium on User Interface Software and Technology, 2004)
A novel touch screen technology is presented. TouchLight uses simple image processing techniques to combine the output of two video cameras placed behind a semi-transparent plane in front of the user. The resulting image shows objects that are on the plane. This technique is well suited for application with a commercially available projection screen material (DNP HoloScreen) which permits projection onto a transparent sheet of acrylic plastic in normal indoor lighting conditions. The resulting touch screen display system transforms an otherwise normal sheet of acrylic plastic into a high bandwidth input/output surface suitable for gesture-based interaction.